2004
DOI: 10.1177/0091270004269236
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Clofarabine, a Second‐Generation Nucleoside Analog, in Pediatric Patients With Acute Leukemia

Abstract: The population pharmacokinetics of plasma clofarabine and intracellular clofarabine triphosphate were characterized in pediatric patients with acute leukemias. Traditional model-building techniques with NONMEM were used. Covariates were entered into the base model using a forward selection significance level of .05 and a backwards deletion criterion of .005. Model performance, stability, and influence analysis were assessed using the nonparametric bootstrap and n-1 jackknife. Simulations were used to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 19 publications
(30 reference statements)
5
36
0
Order By: Relevance
“…31 have fit clofarabine single-agent PK data derived from 3 clinical trials (i.e. the ID99-383 study recruiting pediatric hematologic malignancies, the CLO-212 study in pediatric ALL, and the CLO-222 study in pediatric refractory AML) using a non-parametric LOESS fit to the observed dose normalized concentration-time plot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 have fit clofarabine single-agent PK data derived from 3 clinical trials (i.e. the ID99-383 study recruiting pediatric hematologic malignancies, the CLO-212 study in pediatric ALL, and the CLO-222 study in pediatric refractory AML) using a non-parametric LOESS fit to the observed dose normalized concentration-time plot.…”
Section: Resultsmentioning
confidence: 99%
“…(B) A scatter plot for clofarabine plasma concentrations as measured by LC-MS/MS (in color) overlaid on the pharmacokinetic model developed by Bonate et al . 31 (in gray) for single agent clofarabine in 3 previous clinical studies (ID99-383, CLO-212 and CLO-222) fitted using non-parametric LOESS fit.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic clearance and volume of distribution at steady-state in paediatric patients were estimated to be 28.8 l/h/m 2 and 172 l/m 2 , respectively. The terminal half-life was estimated to be 5.2 h. No apparent differences in pharmacokinetics were observed between patients with ALL or AML, or between males and females [14].…”
Section: Pharmacology/pharmacokineticsmentioning
confidence: 90%
“…While the observed increase in clofarabine plasma concentration in cases of a WBC decrease does not seem to be significant enough to justify modification of the treatment regimen as a function of WBC count, administration of the dose on a per square meter or per body weight basis is crucial. 38 Clofarabine is 47% bound to plasma protein, of which 27% is serum albumin, resulting in wide tissue distribution. 39 Once intracellular, accumulation of clofarabine triphosphate, the active form of clofarabine, in the blasts of patients with refractory leukemia has been demonstrated in several studies.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…39 Once intracellular, accumulation of clofarabine triphosphate, the active form of clofarabine, in the blasts of patients with refractory leukemia has been demonstrated in several studies. 37,38 Because the highest concentrations of dCK are found in lymphoid tissues, a sustained antileukemic activity would be expected, 38 enhanced by the prolonged intracellular half-life of 24 hours for clofarabine triphosphate, in contrast with fludarabine and cladribine, which have median half-lives of only 8-10 hours. 18,37 Based on 24-hour urine collection, 49%-60% of the dose is excreted in the urine unchanged.…”
Section: Mechanism Of Actionmentioning
confidence: 99%